Thermal characteristic reliability of fatty acid binary mixtures as phase change materials (PCMs) for thermal energy storage applications - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M.; Ong H.C. (Elsevier Ltd, 2023)
Binary mixtures; Bins; Chemical bonds; Chemical stability; Energy storage; Eutectics; Fatty acids; Fourier transform infrared spectroscopy; Heat storage; Mixtures; Palmitic acid; Saturated fatty acids; Thermal cycling; Thermal energy; Thermodynamic properties; Chemical bonding structures; Differential scanning calorimetric; Economic feasibilities; Eutectic mixture; Fourier transform infra red (FTIR) spectroscopy; Latent heat of fusion; Thermal characteristics; Thermal Performance; Phase change materials